REFLEXIONES EN TORNO A LA SOSTENlBlLlDAD DE LA DEHESA - Pérez-Díaz, A (Geographicalia, 2005)
In tlie last century roorii tlie Spanisli deliesa llave wakened up a scien- tific interest tliat he only finds paragon and justification in tlie growing concern of tlie public opinion Sor the conservation and restoration of the environnient. In little time, tlie nieadow has passed of being tlie paradigrn of tlie .'latifun- disruo" in its inost pejorative conception, to hecorne an unquestionahle moclel of sustainable developinent. Witliout denying this new conception a priori; tliis article tries to offer the keys Sor a reflection on tlie last sostenibilidad, present ancl f~ic~ire of the rneadow. And he seeks to make it fi-0111 a geograpliical, inte- grative perspective, far froin íleeting fasliions ancl stereotyped opinions
Keywords: Dehesa; economy; land-use systems; s~istainability

REFLEXIONES EN TORNO A LA SOSTENlBlLlDAD DE LA DEHESA - Pérez-Díaz, A. (Geographicalia, 2005)
In tlie last century roorii tlie Spanisli deliesa llave wakened up a scien- tific interest tliat he only finds paragon and justification in tlie growing concern of tlie public opinion Sor the conservation and restoration of the environnient. In little time, tlie nieadow has passed of being tlie paradigrn of tlie .'latifun- disruo" in its inost pejorative conception, to hecorne an unquestionahle moclel of sustainable developinent. Witliout denying this new conception a priori; tliis article tries to offer the keys Sor a reflection on tlie last sostenibilidad, present ancl f~ic~ire of the rneadow. And he seeks to make it fi-0111 a geograpliical, inte- grative perspective, far froin íleeting fasliions ancl stereotyped opinions
Keywords: Dehesa; economy; land-use systems; s~istainability